ORGANIZATIONAL AND ECONOMIC MECHANISM OF SHAPING THE SYSTEM OF INTERNAL ENVIRONMENTAL AUDIT - Lebedevych , Svitlana (Forestry, Forest, Paper and Woodworking Industry, 2012)
The article underlines the need for shaping the system of internal environmental audit in businesses as being a topical issue. A science-based definition of the internal environmental audit has been proposed. Also presented here are the classification of techniques for the internal environmental audit and models of its planning and conducting.